The unprecedented M d = 4.4, 2024, Campi Flegrei earthquake highlights the fluids contribution to the ongoing unrest - Nicola Alessandro Pino; Stefania Danesi; Giacomo Rapagnani; Valerio De Rubeis; Simone Cesca (Communications Earth & Environment)
Abstract The Campi Flegrei caldera has been experiencing volcanic unrest since 2005, rising concern in the population and in local and national authorities. On May 20, 2024, the largest local earthquake ever instrumentally recorded up to that time produced substantial damage, forcing the evacuation of tens of buildings west of the epicenter. At Campi Flegrei, M > 4 earthquakes are rare and their analysis is crucial to understand the unrest dynamics and the relation between rupture and ground shaking pattern, which is essential to mitigate the damage of future earthquakes. We analyse seismic waveforms at local to regional distances to reconstruct the source geometry and kinematics. We estimate millimetric to submillimetric coseismic surface subsidence – below the sensitivity of any standard geodetic technique – which, compared to the general uplift, highlights the crucial role of deep pressurized fluids in earthquakes’ generation. Our results also indicate that rupture directivity and local amplification determined the damage distribution.